A Novel Combination of Genes Causing Temperature-Sensitive Hybrid Weakness in Rice - Than Kutay Soe; Kunieda, Mai; Sunohara, Hidehiko; Inukai, Yoshiaki; Reyes, Vincent Pamugas; Nishiuchi, Shunsaku; Doi, Kazuyuki (Frontiers in Plant Science, 2022)
Reproductive isolation is an obstacle in plant breeding when distant cross is demanded. It can be divided into two main types based on different growth stages: prezygotic and postzygotic isolations. Hybrid sterility and hybrid weakness, which are subtypes of postzygotic isolations, are observed in F1 hybrids. On the other hand, hybrid breakdown is observed in the F2 or later generations through sterility or weakness phenotype. In order to overcome the reproductive barriers, it is necessary to elucidate its mechanism. In this study, genetic analysis for low temperature-dependent hybrid weakness was conducted in a rice F2 population derived from Taichung 65 (T65, Japonica) and Lijiangxintuanheigu (LTH, Japonica). The weak plants in F2 showed short stature, late heading, reduced panicle number, yield decrease, and impaired root development in the field. Our result also showed that hybrid weakness was affected by temperature. It was observed that 24 °C enhanced hybrid weakness, whereas 34 °C showed recovery from hybrid weakness. In terms of morphology of the embryos, no difference was observed. Therefore, hybrid weakness affects postembryonic development and is independent of embryogenesis. The genotypes of the 126 F2 plants were determined by GBS and a linkage map consisting of 1869 single nucleotide polymorphism markers was obtained. Two major QTL were detected on chromosomes 1 (hybrid weakness j 1 (hwj1)) and 11 (hybrid weakness j 2 (hwj2)). Further genotyping indicated that the hybrid weakness was due to an incompatible interaction between T65 allele of hwj1 and LTH allele of hwj2. The large F2 populations consisting of a total of 5722 plants were used for fine mapping of hwj1 and hwj2. The two loci, hwj1 and hwj2, were mapped in regions of 65 kb on chromosome 1 and 145 kb on chromosome 11, respectively. The 65 kb region for hwj1 contained 11 predicted genes, while two disease resistance-related genes were contained in the 23 predicted genes of the hwj2 region. Identified genes along these regions serve as pre-liminary information on the molecular networks associated with hybrid weakness in rice.